The Combination of Extraction and Chronocoulometry of a Solid Precipitate for Teaching a Novel Approach of Electroanalysis - Paez-Collio, M; Paez-Collio, M; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Gulppi-Cabra, M; Gulppi-Cabra, M; Azocar-Guzman, M; Azocar-Guzman, M (Springer Science and Business Media Deutschland GmbH, 2024)
In this study, we introduce an innovative approach to electroanalysis that combines solvent extraction and chronocoulometry for the quantification of furosemide, a loop diuretic medication. The objective of this report is to provide students with a practical learning experience in the field of electroanalysis, enabling them to explore recent developments both theoretically and in the laboratory. The experimental procedure involves the extraction of furosemide from a pharmaceutical tablet using methanol, followed by the deposition of the extracted compound onto an electrode. Chronocoulometry is then employed to determine the quantity of furosemide. A 95% recovery rate and a close to 99% fit between theoretical and experimental substance amounts demonstrate the applicability of the method. This approach offers several didactic benefits for students: (i) It teaches the theory and application of chronocoulometry. (ii) It emphasizes the advantage of chronocoulometry as a calibration-free technique. (iii) It introduces students to the principles of electrochemical stripping techniques. (iv) It demonstrates that solid particles can be effectively studied using electroanalysis. Finally, (v) it provides a real-world application of electroanalysis in quantifying an organic compound. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2023. corrected publication 2024.